1995
DOI: 10.1111/j.1095-8649.1995.tb01617.x
|View full text |Cite
|
Sign up to set email alerts
|

Thermal related variations of seasonal and daily spawning periodicity in Barbus barbus

Abstract: In 1993, nocturnal spawning activities were observed in the diurnal spawning cyprinid Barbus barbus. This behaviour is interpreted as a response to exceptionally high daily thermal amplitudes, regarded as the sign of an unpredictable environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 6 publications
1
18
0
Order By: Relevance
“…This distinct activity pattern, with a peak of activity at twilight, has been observed previously in several species (red morrow, Cheilodactylus fuscus, Lowry and Suthers, 1998; the seabass, Dicentrarchus labrax, Bégout and Lagardère, 1995;Bégout-Anras et al, 1997;Bégout-Anras and Lagardère 1998; the brown trout Salmo trutta, Ovidio et al, 1998Ovidio et al, , 2002. Nocturnal and crepuscular activity was usually suggested to be a response to reduced predation risk (Heggens et al, 1993;Jonsson and Jonsson, 1993), an adaptation to prey availability, or optimal foraging strategy in relation to the water temperature (Baras, 1995). For S. salpa, it would be necessary to track more individuals in different seasons to interpret this particular behaviour pattern.…”
Section: Discussionmentioning
confidence: 99%
“…This distinct activity pattern, with a peak of activity at twilight, has been observed previously in several species (red morrow, Cheilodactylus fuscus, Lowry and Suthers, 1998; the seabass, Dicentrarchus labrax, Bégout and Lagardère, 1995;Bégout-Anras et al, 1997;Bégout-Anras and Lagardère 1998; the brown trout Salmo trutta, Ovidio et al, 1998Ovidio et al, , 2002. Nocturnal and crepuscular activity was usually suggested to be a response to reduced predation risk (Heggens et al, 1993;Jonsson and Jonsson, 1993), an adaptation to prey availability, or optimal foraging strategy in relation to the water temperature (Baras, 1995). For S. salpa, it would be necessary to track more individuals in different seasons to interpret this particular behaviour pattern.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the circadian clock of freshwater fish shows more plasticity than its marine counterpart, which implies that freshwater fish might modify their activity pattern, even changing their nocturnal behavior to diurnal if needed and vice versa (Helfman, 1981;Cook and Bergersen, 1988;Baras, 1995;Naruse and Oishi, 1996). However, recent studies have concluded that circadian activity rhythms in tench are driven by an internal circadian clock, which is, however, strongly influenced by light.…”
Section: Introductionmentioning
confidence: 99%
“…Around Lake Tana, rains usually start late in the afternoon causing a fast rise in the tributaries' water level which has decreased again the following morning. This probably explains why Lake Tana labeobarbs are nocturnal spawners, unlike other barbs (e.g., Barbus barbus, Baras, 1995). The lower risk of predation in shallow waters during the night (Dgebuadze et al, 1999) might also be involved.…”
Section: Migrationmentioning
confidence: 99%